Teacher-Principal Ethnoracial Matching, Geography, and Novice Teacher Career Outcomes - Wesley Edwards; Cornelius Q. Anderson (SAGE Publishing, 2023)
Nationally, many school districts are facing a teacher workforce sustainability crisis, and job retention for novice teachers of color is a key area of focus for educational leaders and policymakers. In this study, we draw on nine years of administrative data from Texas K-12 public schools to better understand how teacher-principal ethnoracial matching is associated with patterns of teacher retention and system-exit. Teacher labor markets are geographically small, so we link data from the National Center for Education Statistics containing geographic locale information to explore how the relationship between ethnoracial matching and novice teacher career outcomes varies across urban, suburban, rural, and town school contexts. We find that matching is associated with an increase in the probability of retention and a decrease in the probability of system-exit, with important variation for novice Black and Latinx teachers working in some nonurban school locales.